Values in Education: An Astounding Wealth of a Nation in the Contemporary World - Quazi, Afshan Naz (Voices of Teachers and Teacher Educators, 2021)
If education is the right of every learner in equipping himself to face challenges in life, then the values are the individual principles or qualities that guide his journey through the rough and tumbles of life. The education in its full essence is the process of transmitting values in the learner and developing human personality in all its dimensions as physical, intellectual, social, ethical and moral development. Good education is inconceivable if it fails to inculcate values essential to social well-being for an honourable life. Values are the great foundations on which our society dwells and an organisational culture is constructed and a social decorum is maintained. They are the invisible wealth of a community and of a nation in determining, guiding and reforming behaviour of the citizens of the country. The history of humanity is to a large extent the history of values and where education defines the methodical unified efforts made towards learning basic facts about humanity. Any educational process devoid of such values will ultimately tarnish the glory of a nation in coming times. Exemplary citizens are made and not born. Education paves the way for captivating values. It would be rather difficult to build a dignified nation without adding values in their resources say human too. True power of value-education lies in ethical principles such as respect, honesty, empathy, equality, solidarity and critical thinking signifying quality tags that should be exemplified and dissipated at every phase during learning cycle of pupils. This research article is focused on the perspectives of value laden quality teaching that manifests intellectual depth, self-reflection, rational thinking that are fundamentals to live in harmony and sustaining overall progress. The article addresses the positive correlational approach among value education, quality education and development of human resources. It advocates to address the loopholes in education system thus, ensuring a schematic framework full of resources for building well-mannered, emotionally-balanced, scholarly-productive, ethically and spiritually value-enriched future society contributing towards morally strong and academically skilled learners beyond the surface factual learning. Hence insights of value education offer newer probes in curriculum and academic agendas of present world.